Comprehensive assessment of 2G bioethanol production. (October 2020) - Sharma, Bhawna; Larroche, Christian; Dussap, Claude-Gilles
Highlights: Production of 2G bioethanol remains technologically challenging. 2G bioethanol production is increasing but still less than 3% of total bioethanol. The biochemical route must tackle with both pentose and hexose conversion. The evaluation of a treatment pathway includes process simulation. Agro-resource renewal and soil impacts are added for a complete LCA. Abstract: The advancements in second-generation bioethanol produced from lignocellulosic biomass, such as crops residues, woody crops or energy grasses are gaining momentum. Though, they are still representing less than 3% of total bioethanol production, the GHG reduction potential is higher than for 1G-bioethanol. The environmental impacts of bioethanol production are totally dependent on feedstock availability and conversion technology. The biochemical conversion route must overcome several technological and economical challenges such as pre-treatment, fermentation, hydrolysis process and separation. A completely mature technology is still to be developed and must adapted to the nature of the feedstock. Nevertheless, using process simulation software, Life Cycle Assessment and integrating the different steps of bioresource harvesting and treatment processes, including the energy balances and the water requirements, it is shown that 2G bioethanol production will reduce environmental impacts provided the evaluation addresses a long-time perspective, including all conversion steps and the regeneration of the bioresource.